Social Interventions in Education to Enhance Students’ Understanding of Juvenile Delinquency - Pratidina Ekanesia; Rifqi Farisan Akbar (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to examine the influence of guidance and counselling programs on students' understanding of juvenile delinquency in a vocational high school in Bandung. Juvenile delinquency is a social problem that often arises in schools and can hinder the development of students' character. Guidance and counselling services are expected to act as preventive measures, increasing students' awareness and understanding of deviant behaviour and its negative consequences. This study used a quantitative, one-group pretest-posttest design with 329 students. The research instrument was a questionnaire designed to measure students' understanding of juvenile delinquency before and after receiving guidance and counselling services. Data analysis was carried out using a paired-samples t-test in SPSS version 25. The analysis showed a significant increase in students' understanding after participating in the guidance and counselling program, with a t-value of -39.85 and p = 0.000 (p < 0.05). These findings prove that the guidance and counselling program is effective in increasing students' awareness and understanding of various forms of juvenile delinquency and their impacts. Therefore, this study recommends strengthening the implementation of guidance and counselling programs as a preventive strategy to address deviant behaviour in schools.